Gender and agricultural innovation in Oromia region, Ethiopia: From innovator to tempered radical - Farnworth, Cathy Rozel; López, Diana E.; Badstue, Lone B.; Hailemariam, Mahelet; Abeyo, Bekele G. (Informa UK Limited, 2018)
This paper explores whether the concept of tempered radicals provides a useful analytic lens through which the strategies of women and men farmer innovators, who are ‘doing things differently’ in agriculture, can be interpreted. The paper uses research data derived from two wheat-growing communities in Oromia Region, Ethiopia. The findings demonstrate that women and men innovators actively interrogate and contest gender norms and extension narratives. Both men and women innovators face considerable challenges, but women in particular are precariously located ‘outsiders within,’ negotiating carefully between norm and sanction.